AGING STRONG 2020: IMPROVING THE HEALTH AND WELL-BEING OF OLDER ADULTS. (11th November 2018) - Tkatch, R; Wicker, E; Martin, D
Abstract: The working definition of successful aging continues to evolve and includes many psychological and social aspects of health and well-being. AARP and UnitedHealthcare, providing AARP® Medicare Supplement plans insured by UnitedHealthcare, are committed to the health and well-being of insureds in their plans, recognizing that health and wellness need to be promoted on a holistic level to ensure successful aging. As part of this commitment a research initiative entitled Aging Strong 2020 has been developed. The purpose of this initiative is to impact members' personal and social investments in their well-being and to integrate these findings into various population health management programs. To accomplish this, a series of interventions over the next three years will aim to increase resilience by focusing on enhanced purpose in life, social connectedness, and optimism. The overarching goal is to improve clinical and psychological health outcomes and participants' satisfaction with health care. The purpose of this symposium is to discuss the overall objectives of Aging Strong 2020, data that informed this initiative, projects that have been developed and launched and their initial findings. Data include a large national survey of older adults across health status categories and examine the prevalence of resilience, purpose in life, and social support. Initial interventions include an expressive writing initiative to improve optimism and purpose in life; a "LifeBio" reminiscent memory program to reduce loneliness; and a mobile application activity to improve purpose in life. The interventions of Aging Strong 2020 provide opportunity to improve the well-being of older adults.